THE EFFECT OF COMPUTER SELF-EFFICACY, COMPETENCE, AND WORK ENVIRONMENT ON THE PERFOMANCE OF UNISNU JEPARA EDUCATIONAL STAFF - Shofia, Nur Lailatus; Fu’ad, Eko Nur (Universitas Nusa Cendana, 2025)
This research aims to analyze the effect of computer self-efficacy, competence, and work environment on the performance of UNISNU Jepara educational staff. This study uses quantitative methodology involving 62 educational staff as samples, with data collected through questionnaires and distributed directly to respondents. Data analysis was carried out using Partial Least Square 3.0 software. The results showed that computer self-efficacy and competence have a significant influence on the performance of educational staff. Meanwhile, the work environment does not directly affect performance but has a significant influence on competence. This indicates an indirect effect of the work environment on performance through competence. Further findings also tested age as a control variable for computer self-efficacy. These results indicate that increasing computer self-efficacy is in line with improving the performance of educational staff. However, efforts to improve performance will be more effective if supported by competency development and a supportive work environment so that the performance of educational staff can reach a more optimal level. Keywords: Computer Self-Efficacy; Competence; Work Environment; Perfomance